Strengthening Country Commitment to Human Development: Lessons from Nutrition - Heaver, Richard (Washington, DC: World Bank, 2012)
Malnutrition persists in most developing countries. It contributes to the deaths of 3.4 million children annually and reduces the intelligence, health, and productivity of those who survive. Nutrition programs-indeed all human development programs-succeed or fail depending in part on the commitment of politicians, bureaucrats, and communities to properly implement them, both initially and over the long term. Technical, economic, and organizational issues get the lion's share of attention in designing nutrition and other human development programs. But the success of such programs often depends on two variables: whether countries back them with adequate financing and whether countries sustain a commitment to high-quality implementation. This book argues that assessing and strengthening country commitment should therefore become a new field of systematic professional practice. This new field requires expertise in political and policy analysis, organizational behavior, and strategic communication. Focusing on a variety of country programs in nutrition-both successful and failed-the book describes practical ways to assess and strengthen commitment and outlines an agenda for learning by doing. In addition to political will, programs need to build support and commitment across government and civil society, from local leaders to parents. To sustain that commitment, organizational structures and processes must be designed to motivate communities and officials over the 15 to 20 years it takes to successfully implement a national nutrition program. This book will especially appeal to those in the fields of nutrition, public health, community and economic development, and political science.